A materialização dos direitos sexuais e reprodutivos das mulheres em São Borja: contribuições para o debate - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This Course Conclusion, results from the experience of the Supervised Internship in Social Work I and II, in the Municipal Center of Specialized Attendance (CEMAE), São Borja / RS. The study presents the materialization of sexual and reproductive rights, contributing to the debate about the intervention of the Social Service for the defense of these rights in the scope of health. Grounded by the Critical Dialectic Method, it focuses on the theoretical categories: Historicity, Totality and Contradiction. The general objective was: To problematize the intervention of the social worker in the defense of the sexual and reproductive rights of the woman, in order to reflect on how these rights are being guaranteed. It was intended to briefly bring up the historical trajectory of women's sexual and reproductive rights in order to better understand this process, as well as to recognize who were the protagonists of this struggle. Through the internship experience, the objective was to learn about the reality of São Borja in relation to the sexual and reproductive rights of women. As well as to explain how the intervention of Social Work as a profession in this process has been carried out. The methodology that sustains this experience report is based on bibliographical and documentary research (participant observations in loco), institutional analysis, reports and field diaries, which describe the moments in which the trainee observed the practice of the social assistant field supervisor and also carried out intervention activities in the field of internship. The results of the study showed that despite the difficulties faced, the social worker plays a fundamental role, along with other professionals, in the process of accessing and guaranteeing the sexual and reproductive rights of women in São Borja.
Keywords: Serviço Social; Direitos das mulheres; Liberdade sexual; Mulheres; Social service; Women's Rights; Sexual freedom; Women; CNPQ::CIENCIAS SOCIAIS APLICADAS